2009
DOI: 10.1002/mrc.2542
|View full text |Cite
|
Sign up to set email alerts
|

7Li NMR chemical shift titration and theoretical DFT calculation studies: solvent and anion effects on second‐order complexation of 12‐crown‐4 and 1‐aza‐12‐crown‐4 with Lithium cation in several aprotic solvents

Abstract: (7)Li NMR titration was used to determine stepwise complexation constants for the second-order complexation of lithium cation with 12-crown-4 in acetonitrile, propylene carbonate and a binary mixture of propylene carbonate and dimethyl carbonate. The anions used were perchlorate, hexaflurophosphate and trifluromethanesulfonate. A second ligand 1-aza-12-crown-4 was similarly investigated. The exchange between the free and complexed cation in these reactions is fast on an NMR timescale resulting in a single lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We first validated this strategy by studying the water solvation using 7 Li and 1 H NMR (Figure a). As the crown ether/Li + ratio increases closer to 1, the chemical shift for 7 Li was found to be downfield (higher chemical shift), indicating a change of the Li + solvation shell and its association with the crown ether molecules . The opposite trend was found for the 1 H signal from H 2 O, for which the chemical shift undertakes an upfield, demonstrating a greater electronic density.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We first validated this strategy by studying the water solvation using 7 Li and 1 H NMR (Figure a). As the crown ether/Li + ratio increases closer to 1, the chemical shift for 7 Li was found to be downfield (higher chemical shift), indicating a change of the Li + solvation shell and its association with the crown ether molecules . The opposite trend was found for the 1 H signal from H 2 O, for which the chemical shift undertakes an upfield, demonstrating a greater electronic density.…”
Section: Introductionmentioning
confidence: 88%
“…As the crown ether/Li + ratio increases closer to 1, the chemical shift for 7 Li was found to be downfield (higher chemical shift), indicating a change of the Li + solvation shell and its association with the crown ether molecules. 33 The opposite trend was found for the 1 H signal from H 2 O, for which the chemical shift undertakes an upfield, demonstrating a greater electronic density. From these observations, it can be concluded that free water molecules are released when adding 12-Crown-4 to the electrolyte following the reaction:…”
Section: ■ Introductionmentioning
confidence: 95%
“…[29][30][31] The interaction of anions with the polymer linkages in the PTB mitigates the influence of electron cloud density on Li + ions, resulting in a downfield shift of the 7 Li peak, while the hydroxyl groups in the original PVA chains renders the upshift of the 7 Li peak. [32,33] In the FTIR spectra (Figure 1c), apparent changes in the ─CF 3 stretching peaks from the TFSI − can be observed after introducing different components to the base electrolyte. The effect of ─OH groups in PVA brings a blue shift of the ─CF 3 peak, while the TDI-caused ─OH content decrease enables the back shift of the peak.…”
Section: Resultsmentioning
confidence: 99%
“…As the ether concentration increases, the 7 Li resonance is shifted downfield and reaches a maximum (À0.8 ppm) in slice 12, where the 12-crown-4 and LiClO 4 concentrations are approximately equal and thus the [Li(12-crown-4)] + complex dominates. 18 In the presence of an excess of 12-crown-4, the 7 Li resonance is then shifted again upfield until it reaches À1.2 ppm in slice 19 (7-fold excess, [Li(12-crown-4) 2 ] + ). The resulting titration curve (see ESI †) fully agrees with previous reports.…”
mentioning
confidence: 99%
“…This broadening could be overcome by further decreasing the slice width, thereby increasing the spatial resolution along the tube axis, but at the cost of reduced sensitivity, which may render weaker signals undetectable. 18,19 The application of slice-selective NMR spectroscopy to reaction monitoring is demonstrated with the reaction between nBuLi and PMDTA. Due to the high reactivity of organolithium reagents and to prevent rapid convection and/or diffusion out of the active sample volume, nBuLi was first diffused into a polystyrene gel matrix, and all steps of the preparation were carried out strictly under argon atmosphere.…”
mentioning
confidence: 99%